Polysiloxane elastic waterproof coating and preparation process thereof
By introducing acrylic resin, composite modified carbon nanotubes and talc powder into polysiloxane coatings, polysiloxane elastic waterproof coatings are prepared, which solves the problems of insufficient waterproof performance and ultraviolet aging of existing coatings, and achieves a coating with high adhesion, good tensile performance and long life.
Patent Information
- Application Number
- CN202510053394.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing polysiloxane coatings have shortcomings in waterproofing performance, which causes moisture to penetrate into the matrix structure, damage the structural strength and stability. At the same time, the coating has a short service life under ultraviolet irradiation and is prone to cracking.
The preparation process of polysiloxane elastic waterproof coating is adopted, and materials such as methyl polysiloxane resin, acrylic resin, composite modified carbon nanotubes and talc powder are mixed and stirred to form a coating with good dispersion and compatibility, thereby improving the waterproof performance and anti-aging properties of the coating.
The high adhesion, good tensile performance and excellent waterproof performance of the polysiloxane coating are achieved, while the service life is extended under ultraviolet light irradiation, avoiding the problem of cracking and falling off of the coating.
Smart Images

Figure BDA0005240634100000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a polysiloxane elastic waterproof coating and a preparation process thereof. Background Art
[0002] Polysiloxane is a polymer with Si-O-Si bond as the main chain. Polysiloxane coatings have excellent weather resistance, chemical resistance and low thermal expansion coefficient. These characteristics make it widely used in the fields of corrosion protection and protection of bridges, oil drilling platforms, ships and aerospace. In recent years, with the application of nanotechnology and functional additives, the performance of polysiloxane coatings has been significantly improved, including enhanced resistance to ultraviolet radiation, longer service life and better adhesion. In addition, the development of environmentally friendly water-based polysiloxane coatings has reduced the emission of volatile organic compounds (VOCs) and met the needs of green buildings and industrial coatings. However, pure polysiloxane coatings have the disadvantages of low film hardness, poor flexibility and low adhesion. The existing common polysiloxane composite coatings with polysiloxane as the main film-forming substance and other polymer resins can improve the hardness, flexibility and impact resistance of polysiloxane coatings to a certain extent.
[0003] CN114836127A discloses a high-toughness polysiloxane composite coating and a preparation method thereof, the preparation method comprising: (1) taking bisphenol A epoxy resin, fused silica powder, dispersant and solvent, mixing, and dispersing at high pressure and high speed; (2) adding methyl polysiloxane resin, adjusting the pressure, heating under high pressure and stirring, slowly adding nano titanium dioxide, and maintaining the pressure to increase the stirring speed; (3) adding titanium dioxide and barium sulfate, mixing, grinding, adding auxiliary agents, and obtaining organic dispersion mixture C; (4) adding a mixture of aminosilane and cobalt cyclopentaneate to the organic dispersion mixture C, and mixing evenly to obtain a polysiloxane composite coating. The polysiloxane composite coating prepared by the invention has a low VOC content, not only significantly improves the curing rate, but also improves the mechanical properties, but has a poor waterproof effect, and moisture may penetrate into the matrix structure, thereby damaging the structural strength and stability of the matrix.
[0004] CN118562384A discloses a room temperature curing organosilicon resin coating and a preparation method thereof. The invention prepares the room temperature curing organosilicon resin coating by mixing hydroxyl organopolysiloxane resin A, alkoxy organopolysiloxane resin B, modified filler and dibutyltin diacetate. The modified filler is prepared by reacting carbon nanotubes as carriers, loading cuprous oxide, and then reacting with alkyltrimethoxysilane and 3-aminopropyltrimethoxysilane. The coating prepared by the invention has the effects of corrosion resistance, high temperature resistance, quick drying at room temperature, etc., but the coating formed by the coating may crack when exposed to long-term ultraviolet rays, and has a short service life. Summary of the invention
[0005] In view of the above-mentioned defects in the prior art, the present invention provides a polysiloxane elastic waterproof coating and a preparation process thereof.
[0006] In order to solve the above technical problems, the present invention provides a preparation process of a polysiloxane elastic waterproof coating, comprising the following steps:
[0007] (1) Mixing methyl polysiloxane resin, dispersant and water, stirring at 60-100 MPa and 1000-1500 rpm for 20-30 min to obtain a mixture A;
[0008] (2) Add acrylic resin, filler, film-forming aid and thickener to mixture A and mix evenly, and stir at 30-50 MPa, 400-600 r / min, and 40-50° C. for 20-50 min to obtain mixture B;
[0009] (3) Add a defoamer and a leveling agent to the mixture B, mix and stir at 500-600 rpm for 20-40 min to obtain a polysiloxane elastic waterproof coating; apply the polysiloxane elastic waterproof coating, and dry to obtain a polysiloxane elastic waterproof coating.
[0010] Preferably, the weight ratio of each raw material component is:
[0011] 35-60 parts of methyl polysiloxane resin, 8-12 parts of acrylic resin, 15-20 parts of filler, 2-5 parts of thickener, 1-3 parts of dispersant, 1-3 parts of film-forming aid, 1-2 parts of defoamer, 1-3 parts of leveling agent, and 10-20 parts of water.
[0012] Preferably, the filler is a mixture of talcum powder and composite modified carbon nanotubes in a weight ratio of 1-3:1.
[0013] Preferably, the method for preparing the composite modified carbon nanotubes comprises the following steps, measured in parts by weight:
[0014] S1. Add 3-6 parts of carbon nanotubes to a mixed acid solution of 350-450 parts of nitric acid and sulfuric acid in a volume ratio of 1:2-3, and stir the solution at 24-26° C. for 12-16 hours to obtain a mixture; then, mix the mixture with water in a weight ratio of 1:4-8 to obtain a mixed solution, filter the mixed solution with a vacuum filter, collect the product, and wash the obtained product with water until the pH reaches neutral; finally, dry the product at 95-105° C. for 1-3 hours to obtain acid-modified carbon nanotubes;
[0015] S2, petroleum ether and sunflower pollen are mixed and stirred at a weight ratio of 1:4-8 for 20-40 minutes, filtered, and then vacuum dried at 55-65°C for 6-10 hours to obtain dried defatted sunflower pollen; then the dried defatted sunflower pollen is mixed with 0.1-0.3g / mL of phosphoric acid aqueous solution at a weight ratio of 1:10-20, refluxed and stirred at 60-80°C for 4-6 hours, filtered, then washed with water, acetone, hydrochloric acid and ethanol in sequence, and dried to a constant weight to obtain sunflower sporopollenin microcapsules;
[0016] S3. Mix 5-8 parts of acid-modified carbon nanotubes, 1-3 parts of sunflower sporopollenin microcapsules and 30-40 parts of isopropanol, and then ultrasonically treat at 300-500 W for 20-30 min, add 0.05-0.2 parts of toluenesulfonic acid under a nitrogen atmosphere, and then stir the mixture at 90-100° C. and 300-600 r / min for 1-3 h, filter, wash, and vacuum dry at 75-85° C. to obtain sunflower sporopollenin microcapsule modified carbon nanotubes, that is, composite modified carbon nanotubes.
[0017] Preferably, the step S3 may also be, by weight:
[0018] 5-8 parts of acid-modified carbon nanotubes, 1-3 parts of sunflower sporopollenin microcapsules and 30-40 parts of isopropanol are mixed, and then ultrasonically treated at 300-500W for 20-30min, 0.0.5-0.2 parts of toluenesulfonic acid are added in a nitrogen atmosphere, and then mixed and stirred at 90-100°C and 300-600r / min for 1-3h, filtered, washed, and vacuum dried at 75-85°C to obtain sunflower sporopollenin microcapsule modified carbon nanotubes; then 3-5 parts of sunflower sporopollenin microcapsule modified carbon nanotubes and 8-15 parts of isopropanol are stirred and mixed, 1-2 parts of amino modifiers and 0.05-0.2 parts of photoinitiator 651 are added, and the mixture is stirred and mixed for 3-5h under ultraviolet irradiation with a wavelength of 365-400nm, filtered, washed, and vacuum dried to obtain composite modified carbon nanotubes.
[0019] Preferably, the amino modifier is selected from one of oleylamine, octadecylamine, N-isopropyloctadecylamine and hexadecylamine.
[0020] Preferably, the thickener is Hemmings 299.
[0021] Preferably, the film-forming aid is propylene glycol methyl ether acetate.
[0022] Preferably, the dispersant is selected from Digo Dispers650, One of Dispers655.
[0023] Preferably, the defoaming agent is selected from one of BYK-092, BYK-141, BYK-01610 and BYK-01615 from Germany.
[0024] Preferably, the leveling agent is selected from one of German BYK-345, BYK-333 and BYK-330.
[0025] As a nano-scale seamless tubular structure carbon material, carbon nanotube has a large specific surface area and excellent mechanical properties. It also has multiple effects such as micro-nano effect and macro quantum tunneling effect, which give it extremely strong adsorption capacity. However, due to the lack of active groups on its surface, large specific surface area and high aspect ratio, it is easy to agglomerate, resulting in difficulty in dispersion in a resin matrix. In order to solve this problem, the present invention first uses a mixed acid solution to modify its surface to introduce carboxyl and hydroxyl groups, and then introduces sunflower sporopollenin microcapsules to react with it. The sunflower sporopollenin microcapsules have a porous structure and surface-rich functional groups, and the hydroxyl and carboxyl groups on the surface of the acid-modified carbon nanotubes can be reacted by the rich functional groups on the surface of the sunflower sporopollenin microcapsules to obtain sunflower sporopollenin microcapsules modified carbon nanotubes, and then introduces an organic amine with a long-chain alkyl group to react with the functional groups on the surface of the sunflower sporopollenin microcapsules modified carbon nanotubes, thereby grafting alkylamine groups on the surface of the modified carbon nanotubes to obtain composite modified carbon nanotubes. The functional groups such as hydroxyl and amino grafted on the surface of the composite modified carbon nanotubes can form hydrogen bonds or covalent bonds with the resin matrix, enhancing the interaction between the composite modified carbon nanotubes and the resin matrix. This interaction can improve the dispersion and compatibility of the carbon nanotubes in the resin matrix, reduce agglomeration, and thus improve the uniformity and performance of the composite material. The introduction of composite modified carbon nanotubes can increase the cross-linking points of the resin system and improve the cross-linking density of the composite material.
[0026] The present invention also finds that the composite modified carbon nanotubes and talcum powder are used in synergistic manner as coating fillers. In the coating preparation process, the functional groups on the surface of the composite modified carbon nanotubes may react with the hydroxyl groups on the surface of the talcum powder by forming chemical bonds to form a stable chemical adsorption layer, thereby changing the chemical properties of the surface of the talcum powder, increasing its compatibility with the resin phase, thereby improving the dispersibility of the talcum powder in the resin, reducing agglomeration, and thus improving the uniformity and mechanical properties of the coating. At the same time, talcum powder is a flaky structure, while carbon nanotubes are tubular structures. The different forms of the two can make them uniformly dispersed and interlaced in the mixed resin during the coating preparation process to form a physical network, which is conducive to further improving the uniformity, waterproofness, anti-aging performance and mechanical properties of the coating.
[0027] The present invention also provides a polysiloxane elastic waterproof coating, which is prepared by the above process.
[0028] In the present invention, talcum powder as a filler can increase the thickness and density of the coating, thereby increasing the contact area between the coating and the substrate and enhancing the adhesion, and its flaky structure can form a physical barrier to prevent water penetration and improve the waterproof performance of the coating. In addition, talcum powder can reflect and scatter ultraviolet rays, reduce the photodegradation of the resin, and thus improve the anti-aging performance of the coating.
[0029] Beneficial effects of the present invention:
[0030] 1. Compared with the prior art, the present invention prepares a polysiloxane elastic waterproof coating by reasonable proportion, utilizing the interaction between various substances, and optimizing the preparation process parameters. After the coating is dried, the polysiloxane elastic waterproof coating is obtained, which not only has strong adhesion but also has good tensile and waterproof properties. Under the irradiation of ultraviolet light, it has a long service life, ensures the overall anti-aging performance, and avoids the problem of cracking and falling off due to long-term use.
[0031] 2. Compared with the prior art, the present invention uses composite modified carbon nanotubes and talcum powder in combination as coating fillers to prepare a polysiloxane elastic waterproof coating. The composite modified carbon nanotubes are not only well dispersed in the polysiloxane elastic waterproof coating and have good compatibility with the system, but also improve the dispersibility of talcum powder in the matrix resin, thereby effectively improving the adhesion, waterproof, tensile and aging resistance of the polysiloxane elastic waterproof coating.
[0032] 3. Compared with the prior art, the preparation process of the present invention has simple steps, low production cost, is environmentally friendly, and has good economic, ecological and social benefits. DETAILED DESCRIPTION
[0033] Parameters for specific chemical substances used, sources.
[0034] Talc, particle size: 10 μm;
[0035] Sunflower powder, mesh number: 100 mesh;
[0036] Methyl polysiloxane resin, item number: SH-5201S, brand: Longsheng Sihai.
[0037] Carbon nanotubes, length: 15 μm, diameter: 15 nm;
[0038] Acrylic resin, solid content: 30%, grade: SEARESIN 142, brand: Sidon.
[0039] Example 1
[0040] A preparation process of a polysiloxane elastic waterproof coating comprises the following steps:
[0041] (1) 45 parts by weight of methyl polysiloxane resin, 2 parts by weight of Dispers 650 and 12 parts by weight of water were mixed, and the mixture was stirred at 80 MPa and 1200 rpm for 25 min to obtain a mixture A;
[0042] (2) 10 parts by weight of acrylic resin, 18 parts by weight of filler, 2 parts by weight of propylene glycol methyl ether acetate and 3 parts by weight of Hemmings 299 were added to mixture A and mixed evenly, and the mixture was stirred at 40 MPa, 500 rpm and 45° C. for 40 min to obtain mixture B;
[0043] (3) Add 1.5 parts by weight of BYK-141 and 2.5 parts by weight of BYK-333 to mixture B, mix and stir at 550 rpm for 30 minutes to obtain a polysiloxane elastic waterproof coating; apply the polysiloxane elastic waterproof coating, and dry to obtain a polysiloxane elastic waterproof coating.
[0044] The filler is a mixture of talcum powder and composite modified carbon nanotubes in a weight ratio of 1:1;
[0045] The preparation method of the composite modified carbon nanotubes comprises the following steps:
[0046] S1. Add 4.5 parts by weight of carbon nanotubes to a mixed acid solution of 400 parts by weight of nitric acid (60 wt%) and sulfuric acid (97 wt%) in a volume ratio of 1:3, and stir the solution at 25°C for 15 hours to obtain a mixture; then, mix the mixture with water in a weight ratio of 1:6 to obtain a mixed solution, filter the mixed solution with a vacuum filter, collect the product, and wash the obtained product with water until the pH reaches neutral; finally, dry the product at 100°C for 2 hours to obtain acid-modified carbon nanotubes;
[0047] S2, petroleum ether and sunflower pollen are mixed and stirred at a weight ratio of 1:6 for 30 minutes, filtered, and then vacuum dried at 62°C for 8 hours to obtain dried defatted sunflower pollen; then the dried defatted sunflower pollen is mixed with 0.2 g / mL phosphoric acid aqueous solution at a weight ratio of 1:16, refluxed and stirred at 70°C for 5.5 hours, filtered, and then washed with water, acetone, hydrochloric acid and ethanol in sequence, and dried to a constant weight to obtain sunflower sporopollenin microcapsules;
[0048] S3. 6 parts by weight of acid-modified carbon nanotubes, 2.5 parts by weight of sunflower sporopollenin microcapsules and 35 parts by weight of isopropanol are mixed, and then ultrasonically treated at 450 W for 25 min, 0.12 parts by weight of toluenesulfonic acid are added under a nitrogen atmosphere, and then mixed and stirred at 98° C. and 450 r / min for 2 h, filtered, washed, and vacuum-dried at 72° C. to obtain sunflower sporopollenin microcapsule-modified carbon nanotubes; then 4.5 parts by weight of sunflower sporopollenin microcapsule-modified carbon nanotubes and 13 parts by weight of isopropanol are stirred and mixed, and 1.5 parts by weight of oleylamine and 0.12 parts by weight of photoinitiator 651 are added, and the mixture is stirred and mixed under ultraviolet irradiation with a wavelength of 365 nm for 4.5 h, filtered, washed, and vacuum-dried to obtain composite modified carbon nanotubes.
[0049] Example 2
[0050] A preparation process of a polysiloxane elastic waterproof coating, which is different from Example 1 in that the filler is a mixture of talcum powder and composite modified carbon nanotubes in a weight ratio of 1:1;
[0051] The preparation method of the composite modified carbon nanotubes comprises the following steps:
[0052] S1. Add 4.5 parts by weight of carbon nanotubes to a mixed acid solution of 400 parts by weight of nitric acid (60 wt%) and sulfuric acid (97 wt%) in a volume ratio of 1:3, and stir the solution at 25°C for 15 hours to obtain a mixture; then, mix the mixture with water in a weight ratio of 1:6 to obtain a mixed solution, filter the mixed solution with a vacuum filter, collect the product, and wash the obtained product with water until the pH reaches neutral; finally, dry the product at 100°C for 2 hours to obtain acid-modified carbon nanotubes;
[0053] S2, petroleum ether and sunflower pollen are mixed and stirred at a weight ratio of 1:6 for 30 minutes, filtered, and then vacuum dried at 62°C for 8 hours to obtain dried defatted sunflower pollen; then the dried defatted sunflower pollen is mixed with 0.2 g / mL phosphoric acid aqueous solution at a weight ratio of 1:16, refluxed and stirred at 70°C for 5.5 hours, filtered, and then washed with water, acetone, hydrochloric acid and ethanol in sequence, and dried to a constant weight to obtain sunflower sporopollenin microcapsules;
[0054] S3. 6 parts by weight of acid-modified carbon nanotubes, 2.5 parts by weight of sunflower sporopollenin microcapsules and 35 parts by weight of isopropanol are mixed, and then ultrasonically treated at 450 W for 25 min, 0.12 parts by weight of toluenesulfonic acid are added under a nitrogen atmosphere, and then mixed and stirred at 98° C. and 450 r / min for 2 h, filtered, washed, and vacuum-dried at 72° C. to obtain sunflower sporopollenin microcapsule-modified carbon nanotubes; then 4.5 parts by weight of sunflower sporopollenin microcapsule-modified carbon nanotubes and 13 parts by weight of isopropanol are stirred and mixed, and 1.5 parts by weight of octadecylamine and 0.12 parts by weight of photoinitiator 651 are added, and the mixture is stirred and mixed under ultraviolet light with a wavelength of 365 nm for 4.5 h, filtered, washed, and vacuum-dried to obtain composite modified carbon nanotubes.
[0055] Example 3
[0056] A preparation process of a polysiloxane elastic waterproof coating, which is different from Example 1 in that the filler is a mixture of talcum powder and composite modified carbon nanotubes in a weight ratio of 1:1;
[0057] The preparation method of the composite modified carbon nanotubes comprises the following steps:
[0058] S1. Add 4.5 parts by weight of carbon nanotubes to a mixed acid solution of 400 parts by weight of nitric acid (60 wt%) and sulfuric acid (97 wt%) in a volume ratio of 1:3, and stir the solution at 25°C for 15 hours to obtain a mixture; then, mix the mixture with water in a weight ratio of 1:6 to obtain a mixed solution, filter the mixed solution with a vacuum filter, collect the product, and wash the obtained product with water until the pH reaches neutral; finally, dry the product at 100°C for 2 hours to obtain acid-modified carbon nanotubes;
[0059] S2, petroleum ether and sunflower pollen are mixed and stirred at a weight ratio of 1:6 for 30 minutes, filtered, and then vacuum dried at 62°C for 8 hours to obtain dried defatted sunflower pollen; then the dried defatted sunflower pollen is mixed with 0.2 g / mL phosphoric acid aqueous solution at a weight ratio of 1:16, refluxed and stirred at 70°C for 5.5 hours, filtered, and then washed with water, acetone, hydrochloric acid and ethanol in sequence, and dried to a constant weight to obtain sunflower sporopollenin microcapsules;
[0060] S3. 6 parts by weight of acid-modified carbon nanotubes, 2.5 parts by weight of sunflower sporopollenin microcapsules and 35 parts by weight of isopropanol are mixed, and then ultrasonically treated at 450 W for 25 min, 0.12 parts by weight of toluenesulfonic acid are added under a nitrogen atmosphere, and then mixed and stirred at 98° C. and 450 r / min for 2 h, filtered, washed, and vacuum-dried at 72° C. to obtain sunflower sporopollenin microcapsule-modified carbon nanotubes; then 4.5 parts by weight of sunflower sporopollenin microcapsule-modified carbon nanotubes and 13 parts by weight of isopropanol are stirred and mixed, and 1.5 parts by weight of N-isopropyl octadecylamine and 0.12 parts by weight of photoinitiator 651 are added, and stirred and mixed for 4.5 h under ultraviolet irradiation with a wavelength of 365 nm, filtered, washed, and vacuum-dried to obtain composite modified carbon nanotubes.
[0061] Example 4
[0062] A preparation process of a polysiloxane elastic waterproof coating, which is different from Example 1 in that the filler is a mixture of talcum powder and composite modified carbon nanotubes in a weight ratio of 1:1;
[0063] The preparation method of the composite modified carbon nanotubes comprises the following steps:
[0064] S1. Add 4.5 parts by weight of carbon nanotubes to a mixed acid solution of 400 parts by weight of nitric acid (60 wt%) and sulfuric acid (97 wt%) in a volume ratio of 1:3, and stir the solution at 25°C for 15 hours to obtain a mixture; then, mix the mixture with water in a weight ratio of 1:6 to obtain a mixed solution, filter the mixed solution with a vacuum filter, collect the product, and wash the obtained product with water until the pH reaches neutral; finally, dry the product at 100°C for 2 hours to obtain acid-modified carbon nanotubes;
[0065] S2, petroleum ether and sunflower pollen are mixed and stirred at a weight ratio of 1:6 for 30 minutes, filtered, and then vacuum dried at 62°C for 8 hours to obtain dried defatted sunflower pollen; then the dried defatted sunflower pollen is mixed with 0.2 g / mL phosphoric acid aqueous solution at a weight ratio of 1:16, refluxed and stirred at 70°C for 5.5 hours, filtered, and then washed with water, acetone, hydrochloric acid and ethanol in sequence, and dried to a constant weight to obtain sunflower sporopollenin microcapsules;
[0066] S3. 6 parts by weight of acid-modified carbon nanotubes, 2.5 parts by weight of sunflower sporopollenin microcapsules and 35 parts by weight of isopropanol are mixed, and then ultrasonically treated at 450 W for 25 min, 0.12 parts by weight of toluenesulfonic acid are added under a nitrogen atmosphere, and then mixed and stirred at 98° C. and 450 r / min for 2 h, filtered, washed, and vacuum-dried at 72° C. to obtain sunflower sporopollenin microcapsule-modified carbon nanotubes; then 4.5 parts by weight of sunflower sporopollenin microcapsule-modified carbon nanotubes and 13 parts by weight of isopropanol are stirred and mixed, and 1.5 parts by weight of hexadecylamine and 0.12 parts by weight of photoinitiator 651 are added, and stirred and mixed for 4.5 h under ultraviolet irradiation with a wavelength of 365 nm, filtered, washed, and vacuum-dried to obtain composite modified carbon nanotubes.
[0067] Example 5
[0068] A preparation process of a polysiloxane elastic waterproof coating, which is different from Example 1 in that the filler is a mixture of talcum powder and composite modified carbon nanotubes in a weight ratio of 1:1;
[0069] The preparation method of the composite modified carbon nanotubes comprises the following steps:
[0070] S1. Add 4.5 parts by weight of carbon nanotubes to a mixed acid solution of 400 parts by weight of nitric acid (60 wt%) and sulfuric acid (97 wt%) in a volume ratio of 1:3, and stir the solution at 25°C for 15 hours to obtain a mixture; then, mix the mixture with water in a weight ratio of 1:6 to obtain a mixed solution, filter the mixed solution with a vacuum filter, collect the product, and wash the obtained product with water until the pH reaches neutral; finally, dry the product at 100°C for 2 hours to obtain acid-modified carbon nanotubes;
[0071] S2, petroleum ether and sunflower pollen are mixed and stirred at a weight ratio of 1:6 for 30 minutes, filtered, and then vacuum dried at 62°C for 8 hours to obtain dried defatted sunflower pollen; then the dried defatted sunflower pollen is mixed with 0.2 g / mL phosphoric acid aqueous solution at a weight ratio of 1:16, refluxed and stirred at 70°C for 5.5 hours, filtered, and then washed with water, acetone, hydrochloric acid and ethanol in sequence, and dried to a constant weight to obtain sunflower sporopollenin microcapsules;
[0072] S3. 6 parts by weight of acid-modified carbon nanotubes, 2.5 parts by weight of sunflower sporopollenin microcapsules and 35 parts by weight of isopropanol are mixed, and then ultrasonically treated at 450 W for 25 min. Then, 0.12 parts by weight of toluenesulfonic acid are added under a nitrogen atmosphere. Then, the mixture is mixed and stirred at 98° C. and 450 r / min for 2 h. The mixture is filtered, washed, and vacuum dried at 72° C. to obtain sunflower sporopollenin microcapsule-modified carbon nanotubes, i.e., composite modified carbon nanotubes.
[0073] Comparative Example 1
[0074] A preparation process of a polysiloxane elastic waterproof coating, which is different from Example 1 in that the filler is a composite modified carbon nanotube;
[0075] The preparation method of the composite modified carbon nanotubes is consistent with that of Example 1.
[0076] Comparative Example 2
[0077] A preparation process of a polysiloxane elastic waterproof coating, which is different from Example 1 in that the filler is a mixture of talcum powder and acid-modified carbon nanotubes in a weight ratio of 1:1;
[0078] The method for preparing the acid-modified carbon nanotubes comprises the following steps:
[0079] 4.5 parts of carbon nanotubes were added to a mixed acid solution of 400 parts of nitric acid (60wt%) and sulfuric acid (97wt%) in a volume ratio of 1:3, and the solution was stirred at 25°C for 15 hours to obtain a mixture; then, the mixture was mixed with water in a weight ratio of 1:6 to obtain a mixed solution, the mixed solution was filtered with a vacuum filter, the product was collected, and the obtained product was washed with water until the pH reached neutral; finally, the product was dried at 100°C for 2 hours to obtain acid-modified carbon nanotubes.
[0080] Comparative Example 3
[0081] A preparation process of a polysiloxane elastic waterproof coating, which differs from Example 1 in that the filler is a mixture of talcum powder and carbon nanotubes in a weight ratio of 1:1.
[0082] Comparative Example 4
[0083] A preparation process of a polysiloxane elastic waterproof coating, which differs from Example 1 in that the filler is talcum powder.
[0084] Test Example 1
[0085] Performance Testing
[0086] The polysiloxane elastic waterproof coating obtained in Examples 1-5 and Comparative Examples 1-4 of the present invention was applied to the surface of the fiber-reinforced cement board specified in the national standard GB / T 9271-2008 "Standard Test Plate for Paints and Varnishes". After conditioning for 24 hours at 25°C and a relative humidity of 50%, a coating with a thickness of 1.5 mm was obtained. This was used as a test plate and the following tests were performed: the adhesion of the sample was tested according to the "GB / T9286-2021 Paint and Varnish Scratching Test"; the tensile properties of the sample were tested according to the standard "GB / T 1040.1-2018 Determination of Tensile Properties of Plastics", and the sample was placed in an ultraviolet wavelength of 313 nm and an irradiance of 0.54 W / m 2The samples were aged in a UV aging box for 120 hours, and then the tensile properties were tested. Deionized water was added to the coating surface formed by the sample through a pinhole syringe, and the water contact angle of the coating was measured using an SDC-100S contact angle tester. The test was performed at 3 different positions on each sample, and each position was measured twice. The average of the 6 values was taken. The test results are shown in Table 1:
[0087] Table 1 Performance test results of various embodiments and comparative examples
[0088]
[0089] As can be seen from Table 1, the adhesion of Examples 1-4 is level 1, all of which show good adhesion, while the adhesion test results of Example 5 and Comparative Examples 1-4 are slightly worse than those of the examples, especially the adhesion level of Comparative Example 4 is 4, indicating that the addition of talcum powder and composite modified carbon nanotubes can improve the adhesion between the coating and the substrate, while the adhesion of the coating without composite modified carbon nanotubes is relatively weak. The reason for this may be that the composite modified carbon nanotubes have nanometer size and a high surface area, and can provide more "mechanical latch" points when used in conjunction with talcum powder, which also has a high specific surface area, which may assist in forming a good mechanical anchoring effect between the coating and the substrate, thereby increasing the adhesion of the coating; at the same time, the composite modified carbon nanotubes introduce hydrophobic long-chain alkylamines and the rich functional groups on the surface of the sunflower spore pollenin microcapsules through chemical modification, which may form hydrogen bonds or chemical bonds with the polar groups on the surface of the substrate, thereby enhancing the adhesion between the coating and the substrate; in addition, the composite modified carbon nanotubes have both hydroxyl groups and amino groups, which may promote the cross-linking reaction of the resin, increase the cross-linking density of the coating, and further improve the cohesion and adhesion of the coating.
[0090] As shown in Table 1, by comparing Examples 1-5 and Comparative Examples 1-4, it is found that the water contact angles of Examples 1-5 are all higher than 150°, wherein the water contact angle of Example 1 is the highest, which is 163°, indicating that the coating has good hydrophobicity, while the water contact angles of Comparative Examples 1-4 are relatively low, especially the water contact angle of Comparative Example 4 is the lowest at 105°, indicating that the addition of talcum powder and composite modified carbon nanotubes can significantly improve the hydrophobicity of the coating, and the coating without composite modified carbon nanotubes has poor hydrophobicity. The reason for the analysis may be that the synergistic use of composite modified carbon nanotubes and talcum powder helps to improve the dispersibility of talcum powder in the matrix resin, can increase the compactness of the coating, and reduce the pores and microcracks in the coating, which can hinder the penetration of water molecules into the interior of the coating, and the long-chain alkylamine structure on the surface of the composite modified carbon nanotubes provides hydrophobicity, increases the contact angle of the coating, and may play a role similar to the lotus leaf effect, so that water forms water droplets on the surface of the coating, thereby improving the waterproofness of the coating. At the same time, the addition of composite modified carbon nanotubes and talc increased the roughness of the coating surface, which further increased the contact angle and exhibited better hydrophobicity.
[0091] As can be seen from Table 1, by comparing Examples 1-5 and Comparative Examples 1-4, it is found that the tensile strength and elongation at break of Examples 1-5 are both higher, indicating that the addition of talcum powder and composite modified carbon nanotubes can improve the mechanical properties of the coating; after aging, the tensile strength and elongation at break of Examples 1-5 are both decreased, but the decrease is small, indicating that the coating has good resistance to ultraviolet aging; the tensile strength and elongation at break of Comparative Examples 1-4 are relatively low, and the decrease after aging is large, indicating that the mechanical properties and ultraviolet aging resistance of the coating without composite modified carbon nanotubes are poor. The reason may be that the carbon atoms in the composite modified carbon nanotubes can absorb the electronic energy level of light of a specific wavelength. When ultraviolet light irradiates the coating, its energy can be absorbed by the electrons in the composite modified carbon nanotubes, causing the electrons to transition from low energy levels to high energy levels, thereby reducing the direct irradiation of ultraviolet light to the matrix resin; at the same time, the composite modified carbon nanotubes are tubular nanoscale structures composed of carbon atoms with a high aspect ratio and a large surface area. Due to their size and shape, the composite modified carbon nanotubes can serve as the center of light scattering. When ultraviolet light irradiates the coating, part of the light will be scattered to other directions by the composite modified carbon nanotubes, reducing the direct irradiation of the coating matrix resin; sunflower sporopollenin microcapsules have a large specific surface area and a complex molecular structure. When they are coated or grafted onto the surface of carbon nanotubes, they can increase the total absorption cross-section of the carbon nanotubes, thereby improving the absorption of ultraviolet rays, and the introduction of sunflower sporopollenin microcapsules may form an uneven surface structure on the surface of carbon nanotubes, thereby improving the scattering effect of ultraviolet rays. Because the composite modified carbon nanotube has a strong absorption and scattering effect on ultraviolet rays, and the composite modified carbon nanotube has good dispersibility and compatibility with the matrix resin, the composite modified carbon nanotube is more evenly distributed in the coating, so as to more effectively absorb and scatter ultraviolet rays, and the ultraviolet radiation intensity received by the matrix resin is significantly reduced, thereby slowing down the photodegradation process and extending the service life of the coating. And the composite modified carbon nanotube may promote the cross-linking reaction of the resin, increase the cross-linking density of the coating, thereby improving the cohesion and tensile strength of the coating. In addition, the composite modified carbon nanotube is used in coordination with talcum powder, and both have excellent mechanical properties, such as high strength and high modulus, and the composite modified carbon nanotube can improve these characteristics and can be directly transferred to the coating, improve its overall tensile strength, and in the coating preparation process, the two can be uniformly dispersed and interlaced in the mixed resin to form a physical network, and the functional groups on the surface of the composite modified carbon nanotube may promote the interaction between the carbon nanotube and the talcum powder, and enhance the stability of the network structure. The existence of the two network structures can disperse and transfer stress when the coating is subjected to external force, reduce stress concentration, and thus further improve the tensile strength and toughness of the coating.
[0092] Comparative Examples 1-4 show that the water contact angle, tensile strength, elongation at break and anti-ultraviolet aging performance of Example 1 using oleylamine as an amino modifier are significantly better than those of Examples 2-4 using octadecylamine, N-isopropyloctadecylamine and hexadecylamine as amino modifiers, respectively, indicating that as the type of amino modifier in the composite modified carbon nanotubes changes, the water contact angle, tensile strength, elongation at break and anti-ultraviolet aging performance of the coating are reduced, among which the coating prepared by applying oleylamine to the composite modified carbon nanotubes shows the best performance. The reason for this may be that oleylamine has a unique long chain and double bond structure, which makes it easier to approach and penetrate the surface of the modified carbon nanotubes when reacting with the surface of the modified carbon nanotubes, forming a more uniform modified layer, thereby giving it excellent dispersibility and hydrophobicity. The long chain alkyl and double bonds of oleylamine not only enhance its flexibility in the matrix, but also effectively form a dense hydrophobic film layer on the surface of the carbon nanotubes. This film blocks the penetration of water molecules through the hydrophobic effect, significantly improves the water contact angle of the coating, and shows excellent waterproof performance. In addition, the long-chain structure of oleylamine forms a strong "mechanical locking" effect between the carbon nanotubes and the matrix. This cross-linked network structure can evenly disperse stress when subjected to force, reduce stress concentration, and thus significantly improve the tensile strength and toughness of the coating. More importantly, oleylamine provides excellent protection in ultraviolet aging environments. Its long-chain double bond structure can scatter ultraviolet light on the surface of carbon nanotubes and slow down the direct degradation of the matrix by ultraviolet rays. This protective effect not only extends the service life of the coating, but also maintains its long-term structural stability.
Claims
1. A process for preparing a polysiloxane elastic waterproof coating, characterized in that: The following steps are involved: (1) Mixing methyl polysiloxane resin, dispersant and water, stirring at 60-100 MPa and 1000-1500 rpm for 20-30 min to obtain a mixture A; (2) Add acrylic resin, filler, film-forming aid and thickener to mixture A and mix evenly, and stir at 30-50 MPa, 400-600 r / min, and 40-50° C. for 20-50 min to obtain mixture B; (3) Add a defoamer and a leveling agent to the mixture B, mix and stir at 500-600 rpm for 20-40 min to obtain a polysiloxane elastic waterproof coating; apply the polysiloxane elastic waterproof coating, and dry to obtain a polysiloxane elastic waterproof coating.
2. The process for preparing the polysiloxane elastic waterproof coating according to claim 1, characterized in that: The weight proportion of each raw material component is: 35-60 parts of methyl polysiloxane resin, 8-12 parts of acrylic resin, 15-20 parts of filler, 2-5 parts of thickener, 1-3 parts of dispersant, 1-3 parts of film-forming aid, 1-2 parts of defoamer, 1-3 parts of leveling agent, and 10-20 parts of water.
3. The process for preparing the polysiloxane elastic waterproof coating according to claim 1 or 2, characterized in that: The filler is a mixture of talcum powder and composite modified carbon nanotubes in a weight ratio of 1-3:
1.
4. The process for preparing the polysiloxane elastic waterproof coating according to claim 3, characterized in that: The preparation method of the composite modified carbon nanotubes comprises the following steps, measured by weight: S1. Add 3-6 parts of carbon nanotubes to a mixed acid solution of 350-450 parts of nitric acid and sulfuric acid in a volume ratio of 1:2-3, and stir the solution at 24-26° C. for 12-16 hours to obtain a mixture; then, mix the mixture with water in a weight ratio of 1:4-8 to obtain a mixed solution, filter the mixed solution with a vacuum filter, collect the product, and wash the obtained product with water until the pH reaches neutral; finally, dry the product at 95-105° C. for 1-3 hours to obtain acid-modified carbon nanotubes; S2, petroleum ether and sunflower pollen are mixed and stirred at a weight ratio of 1:4-8 for 20-40 minutes, filtered, and then vacuum dried at 55-65°C for 6-10 hours to obtain dried defatted sunflower pollen; then the dried defatted sunflower pollen is mixed with 0.1-0.3g / mL of phosphoric acid aqueous solution at a weight ratio of 1:10-20, refluxed and stirred at 60-80°C for 4-6 hours, filtered, then washed with water, acetone, hydrochloric acid and ethanol in sequence, and dried to a constant weight to obtain sunflower sporopollenin microcapsules; S3. Mix 5-8 parts of acid-modified carbon nanotubes, 1-3 parts of sunflower sporopollenin microcapsules and 30-40 parts of isopropanol, and then ultrasonically treat at 300-500 W for 20-30 min, add 0.05-0.2 parts of toluenesulfonic acid under a nitrogen atmosphere, and then stir the mixture at 90-100° C. and 300-600 r / min for 1-3 h, filter, wash, and vacuum dry at 75-85° C. to obtain sunflower sporopollenin microcapsule modified carbon nanotubes, that is, composite modified carbon nanotubes.
5. The process for preparing the polysiloxane elastic waterproof coating according to claim 4, characterized in that: The step S3 may also be, by weight: 5-8 parts of acid-modified carbon nanotubes, 1-3 parts of sunflower sporopollenin microcapsules and 30-40 parts of isopropanol are mixed, and then ultrasonically treated at 300-500 W for 20-30 min, 0.0.5-0.2 parts of toluenesulfonic acid are added under a nitrogen atmosphere, and then mixed and stirred at 90-100° C. and 300-600 r / min for 1-3 h, filtered, washed, and dried in vacuo at 75-85° C. to obtain sunflower sporopollenin microcapsule-modified carbon nanotubes; Then, 3-5 parts of sunflower sporopollenin microcapsule modified carbon nanotubes and 8-15 parts of isopropanol are stirred and mixed, and then 1-2 parts of amino modifier and 0.05-0.2 parts of photoinitiator 651 are added, and the mixture is stirred and mixed for 3-5 hours under ultraviolet irradiation with a wavelength of 365-400 nm, filtered, washed, and vacuum dried to obtain composite modified carbon nanotubes.
6. The process for preparing the polysiloxane elastic waterproof coating according to claim 5, characterized in that: The amino modifier is selected from one of oleylamine, octadecylamine, N-isopropyloctadecylamine and hexadecylamine.
7. The process for preparing the polysiloxane elastic waterproof coating according to claim 1 or 2, characterized in that: The thickener is Hemmings 299; the film-forming aid is propylene glycol methyl ether acetate.
8. The process for preparing the polysiloxane elastic waterproof coating according to claim 1 or 2, characterized in that: The dispersant is selected from Digo Dispers650, Dispers655; the defoaming agent is selected from one of BYK-092, BYK-141, BYK-01610, BYK-01615 of Germany; the leveling agent is selected from one of BYK-345, BYK-333, BYK-330 of Germany.
9. A polysiloxane elastic waterproof coating, characterized in that: Prepared by the process described in any one of claims 1 to 8.
Citation Information
Patent Citations
Composite epoxy resin waterproof coating
CN105199549A
High-wear-resistance water-based plastic coating and preparation method thereof
CN110922839A
Anti-ultraviolet radiation heat-insulating coating as well as preparation method and application thereof
CN117844316A
Water-repellent structure, manufacturing method therefor, and water-repellent coating agent employed in same
US20220372303A1
Cited By
Anti-fouling self-cleaning powder coating and preparation method thereof
CN120230472A
Waterproof fiber composite board and preparation method thereof
CN121179533A
Multifunctional fireproof and waterproof polysiloxane coating and preparation method thereof
CN121343478A